A review of biomaterial as an adsorbent: From the bibliometric literature review, the definition of dyes and adsorbent, the adsorption phenomena and isotherm models, factors affecting the adsorption process, to the use of typha species waste as adsorbent - N'diaye, Abdoulaye Demba; Kankou, Mohamed Sid' Ahmed; Hammouti, Belkheir; Nandiyanto, Asep Bayu Dani; Al Husaeni, Dwi Fitria (Komunitas Ilmuwan dan Profesional Muslim Indonesia, 2022)
This paper presents a review of adsorption isotherms of some dyes from aqueous solutions by biomaterial. In this paper, we reported Typha waste as a model of biomaterial classified as a low-cost adsorbent. The paper also briefly discusses about the literature information from the definition of dyes and adsorbents, bibliometric analysis, adsorption phenomena, adsorption isotherm models, and factors affecting the adsorption, to the use of Typha species waste as a low-cost adsorbent. The operational parameters factors are explained in terms of pH, adsorbent dosage, contact time, and initial dye concentration that will affect the process of removing textile dye. The solution of pH turns out to be the most important condition in the adsorption process for anionic dye, a low pH value are preferable in contrast to cationic dye where the suitable pH value is high. For the adsorbent dose, the adsorption capacity increase along with the increment of adsorbent dosage due to the increase of theavailable amount of adsorption site. The contact time between the adsorbent and dye affects the efficiency of dye removal where a strong attraction force will shorten the time. As for the effect of dye initial concentration, increasing the initial concentration enhances the increment of adsorbent surface area to adsorb dyes. Several isotherm models are described. The Langmuir model is frequently used to evaluate the adsorption capacity of the Typha species waste as adsorbents. This review paper suggested that the accuracy level obtained from adsorption processes is greatly dependent on the successful modeling of adsorption isotherms. Typha biomaterial wastes can be considered as the new useful low-cost natural adsorbents for dye clean-up operations in aquatic systems.